The effectiveness of the seven – cycle learning strategy 7E’s on the achievement and attitude towards the course for students of the Curriculum and Teaching Methods course at Shaqra University in the Kingdom of Saudi Arabia - Alotaibi, Lafa Mohmmed Hilal (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the effectiveness of the seven – cycle learning strategy 7E’s on the achievement and attitude towards the course among the students of the course of curricula and teaching methods at Shaqra University in the Kingdom of Saudi Arabia. To achieve the objective of this study, the semi- experimental was used on a sample of (110) students of the Curriculum and Teaching Methods course (CUR 330), who were divided equally into two groups (experimental and control). Research tools were also prepared, which were an achievement test and an attitude measure toward the course. After adjusting the tools and applying the study experience, it was concluded that there are statistically significant difference between the students of the two groups (experimental and control) in the post- measurement of the achievement test and the attitude scale in favor of the experimental group. Also, between the pre and post measurement of the achievement test and the attitude of the experimental group in favor of the post measurement, and the high effectiveness of the seven- cycle learning strategy role in developing achievement and the attitude towards achievement and direction of the students of the Curriculum and Teaching Methods course (CUR 330). In the light of the results, several recommendations were recommended, the most important of which is the need to train faculty members to use constructive learning strategies, especially the seven- cycle learning, in teaching various courses at the university level.